2022
DOI: 10.3390/ma15196601
|View full text |Cite
|
Sign up to set email alerts
|

Phosphogypsum-Based Ultra-Low Basicity Cementing Material

Abstract: Traditional Portland cement is widely used in the preparation of various hydraulic concrete. However, the high alkalinity produced by cement hydration threatens the survival of aquatic animals and plants. In this paper, a new eco-friendly, ultra-low alkalinity, cementitious material was prepared with industrial waste phosphogypsum, granulated ground blast slag (GGBS) and sulphoaluminate cement. When appropriate proportions are used, the pH value of the test blocks’ pore solutions at different ages were all les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The X-ray photoelectron spectroscopy (XPS) analysis shows that fluorine impurities in phosphogypsum include sodium fluorosilicate, potassium fluorosilicate, fluorophosphoric acid, calcium fluoride, magnesium fluoride, and aluminum fluoride. Using a combination of X-ray photoelectron spectroscopy (XPS) and electron microprobe (EMPA), Zhao et al [90] Li et al [107] pointed out that the content of soluble fluorine in phosphogypsum increases with an increase in gypsum particle size. Peng et al [108] found that soluble fluorine in phosphogypsum is mainly distributed on the surface of gypsum crystals using SEM/EDXA analysis.…”
Section: Fluorine Impuritiesmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy (XPS) analysis shows that fluorine impurities in phosphogypsum include sodium fluorosilicate, potassium fluorosilicate, fluorophosphoric acid, calcium fluoride, magnesium fluoride, and aluminum fluoride. Using a combination of X-ray photoelectron spectroscopy (XPS) and electron microprobe (EMPA), Zhao et al [90] Li et al [107] pointed out that the content of soluble fluorine in phosphogypsum increases with an increase in gypsum particle size. Peng et al [108] found that soluble fluorine in phosphogypsum is mainly distributed on the surface of gypsum crystals using SEM/EDXA analysis.…”
Section: Fluorine Impuritiesmentioning
confidence: 99%
“…The binding material with ultra-low alkalinity based on industrial wastes of phosphogypsum, granulated blast-furnace slag, and sulfoaluminate cement, which was obtained in [26], has a broad application in the construction of islands, reefs, and river restoration. The new type of binder allows the use of a large amount of industrial waste and has the advantages of short setting time, low heat of hydration, high strength of the cement slurry, and the ability to fix harmful substances in phosphogypsum, such as phosphates, fluorides, and Cr and Ba elements.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-granulated blast furnace slag (GGBS) is another frequently used SCM due to its beneficial effect in terms of workability, long-term mechanical properties of mortar and concrete [ 10 ], improved pore structure [ 11 ], reduced shrinkage, and better durability [ 12 ]. The replacement of OPC by phosphogypsum, a by-product of fertilizer manufacturing, has also recently been recognized to have beneficial effects in terms of the elastic, mechanical, and durability properties of mortar and concrete [ 13 , 14 , 15 ]. However, in the case of phosphogypsum, a setting retarder is recommended.…”
Section: Introductionmentioning
confidence: 99%